Analysis of Saudi Arabia Intervention in Decisive Storm Operations in Yemen - Salim, Fajri (Journal of International Relations on Energy Affairs, 2022)
This research analyses the factor that influenced Saudi Arabia's decision to intervene in Yemen's civil conflict through military intervention known as Operation Decisive Storm in 2015. Before 2014, Saudi Arabia always avoided intervening in Yemen's civil conflict. However, there was a behavioral change in Saudi Arabia's policy when they decided to do military intervention in Yemen. Answer this Explanatory research using strategic theory and qualitative research methods. In the analysis of this research, the researcher found that the reason why Saudi Arabia's sudden change to intervene the conflict is influenced by a geographical factor in which there is a potential threat from Houthi rebels to Saudi nearest region that directly borders Yemen and the participation of Saudi Arabia's Political Rival in Regions, Iran, for the battle of hegemony